2019
DOI: 10.18805/lr-4164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Sources of Plant Nutrients on Soil Fertility, Nutrient Uptake and Productivity of Soybean under Vertisols

Abstract: A field experiment was conducted at College of Agriculture (RVSKVV), Indore during kharif 2013 to study the effect of different sources of plant nutrients on productivity, profitability nutrient uptake and soil fertility of soybean in relation to eight nutrient management treatments (T1: RDF- recommended dose of fertilizer (N:P:K:S @ 30:60:30:30 kg/ha), T2: RDF + Rhizobium + PSB (20 g/kg seed), T3: RDF + 50 kg ZnSO4/ha + Rhizobium + PSB, T4: RDF + 1 g (NH4)2MoO4/kg seed + Rhizobium + PSB, T5: RDF + 5 kg Borax/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results revealed that the application of P with HA decreases the P-fixation and increases the water-soluble P availability to plants by making its soluble complexes and its uptake improves the storage of photosynthates in the plants. The addition of humic acid and FYM have direct as well as indirect effects on crop growth and yield, as they play an essential role in supplying and cycling nutrients in the soil and releasing the insoluble pool by its solubilising effect under the P-deficit conditions (Hussain et al, 2021;Kumawat et al, 2021). The FYM and humic acid, besides releasing their own nutrient, increases the nutrient use T 1 +PA 3 ( Phytase+HA)+SSP @ 50% recommended soil test dose FYM-Farmyard manure @ 12.5 t ha -1 , HA-Humic acid @ 3 kg ha -1 , Phytase @ 2 kg ha -1 and PSB-Phosphorus solubilising bacteria @ 2 kg ha -1 .…”
Section: Effect Of P-activators On Maize Yield and P Uptakementioning
confidence: 99%
“…The results revealed that the application of P with HA decreases the P-fixation and increases the water-soluble P availability to plants by making its soluble complexes and its uptake improves the storage of photosynthates in the plants. The addition of humic acid and FYM have direct as well as indirect effects on crop growth and yield, as they play an essential role in supplying and cycling nutrients in the soil and releasing the insoluble pool by its solubilising effect under the P-deficit conditions (Hussain et al, 2021;Kumawat et al, 2021). The FYM and humic acid, besides releasing their own nutrient, increases the nutrient use T 1 +PA 3 ( Phytase+HA)+SSP @ 50% recommended soil test dose FYM-Farmyard manure @ 12.5 t ha -1 , HA-Humic acid @ 3 kg ha -1 , Phytase @ 2 kg ha -1 and PSB-Phosphorus solubilising bacteria @ 2 kg ha -1 .…”
Section: Effect Of P-activators On Maize Yield and P Uptakementioning
confidence: 99%
“…Soybean mainly grown in the rainfed condition and it is important for the livelihood of small and marginal farmers. Soybean contributes 43 per cent to the total oilseeds and 25 per cent to the total oil production in India and ranks fourth in respect to production of soybean in the world (Tomar et al, 2018 andKumawat et al, 2021) In India, average productivity of soybean is low due to lack of seed treatment with bio fertilizers, lack of weed management due to unavailability of labour or continuous rain, lack of sufficient soil moisture due to long dry spells d urin g cro p grow th period , im b alan ced n utrition , improper pest and disease management etc., affect the seed yield and productivity of soybean (Jaybhay et al,2 01 8). In g en eral, to tal ann ual lo ss in ag ricu lture produces, weeds account for 45%, insect 30%, disease 20% and other pests 5% (Rani and Raju, 2020).…”
Section: Introductionmentioning
confidence: 99%